2014
DOI: 10.1590/s0102-86502014000700002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model of Achilles tendon injury in rats

Abstract: Brazil. Intellectual and scientific content of the study, critical revision. ABSTRACT PURPOSE:To describe an effective experimental model to study the Achilles tendon healing. METHODS:Forty male Rattus norvegicus albinus, Wistar lineage adult male weighing 250 to 300g were used for this experiment and thirty were surgically submitted to bilateral partial transverse section of the Achilles tendon. The right tendon was treated with radio waves (RF) whereas the left tendon served as control. On the third postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…During the remodeling stage, the healing tissue is resized and reshaped with the decrease in cellularity and also the collagen and glycosaminoglycan synthesis occurs. [1] According to our results, ABS has negative effect on tendon healing. Up to date, no study was reported about the effects of ABS on tendon healing.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…During the remodeling stage, the healing tissue is resized and reshaped with the decrease in cellularity and also the collagen and glycosaminoglycan synthesis occurs. [1] According to our results, ABS has negative effect on tendon healing. Up to date, no study was reported about the effects of ABS on tendon healing.…”
Section: Discussionmentioning
confidence: 61%
“…But in some studies, tendon healing process has been studied for as long as six weeks in rats. [1] With this present study, the stage at which the ABS affects the healing process is unclear. The euthanization time may be longer or may be studied with three-week and a six-week time periods with more animals.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Transection of the paratenon and Achilles tendon fascicles was achieved with a transverse incision approximately 5 mm proximal to the calcaneal insertion area. [ 7 ] The incised Achilles tendon was re-sutured with atraumatic USP 4/0 silk (Neosilk Ultra, İzmir, Turkey) [Figure 1a and b ]. After the primary repair of the tendon, the rats were released in the cages without immobilization.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-six rats were divided into two groups: a control group and a 532 nm laser group. For the tendon injury model, we adopted a rat model of Achilles-tendon injury following a previously-reported method [19]. The Achilles tendon was separated from the plantaris and soleus tendons and injury were surgically induced by semi-cutting, followed by primary suture repair.…”
Section: Tendon Injury Modelmentioning
confidence: 99%